A Review of the Stimulus–Organism–Response Paradigm and Environmental Education for Cruise Tourism: A Proposed Framework - Chun-Hua Hsiao; Kai-Yu Tang (Advances in Technology Innovation, 2025)
With the rapid growth of the global cruise tourism industry and its increasing environmental impact, there is an urgent need to address sustainability challenges in line with the SDGs, especially in Taiwan. Despite the growing research on environmental education, there is a lack of a theoretical framework from the perspective of the stimulus-organism-response (S-O-R) paradigm that examines the relationships between external stimuli, internal organisms, and individual responses to environmental education in the context of cruise tourism. The proposed framework includes attention to environmental issues and awareness of consequences as external stimuli. These stimuli influence affective and cognitive processes, which are internal states of the organism. In turn, the affective and cognitive states drive pro-environmental behavioral responses. Additionally, the proposed framework incorporates two potential moderating factors: cultural differences and environmental education with emerging technologies. Implications for environmental education in cruise tourism are provided.